Penerapan Sanksi Juru Parkir Liar Atas Pungutan Tarif Parkir Minimarket di Kota Surabaya - Islam, Bunga Putri (Faculty of Law, University of Muhammadiyaha Surabaya, 2023)
Parking includes conditions where the means of transportation or vehicles stop temporarily and the driver is not at the location, but it is undeniable that illegal parking attendants are still often found indirectly forcing us to pay for parking services, especially at minimarkets in the city of Surabaya. The purpose of this study was to determine the role of the Surabaya City government in controlling parking attendants and imposing sanctions on illegal parking attendants in Surabaya City minimarkets. The research method used in this writing is normative research with primary and secondary legal materials. From the results of this study, the Surabaya City government has regulated the implementation of parking through Surabaya City Regional Regulation Number 3 of 2018 concerning the Implementation of Parking in the City of Surabaya. The regional regulation also explains the provisions for official parking officers. Meanwhile, administrative sanctions that can be given to illegal parking attendants at minimarkets can be in the form of a warning, a written warning or even being fired as a parking attendant. And according to Article 39 of the Regional Regulation of the City of Surabaya Number 3 of 2018 concerning the Implementation of Parking, criminal sanctions can be given, such as imprisonment or fines.